Evaluasi Penggunaan Silica+® sebagai Feed Additive terhadap Metabolisme Mineral, Status Kesehatan dan Kualitas Ekskreta Broiler - Gusma Gama Maradon; Sumiati Sumiati; Rita Mutia; Wiwin Winarsih (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
This study aimed to evaluate dietary inclusion of silica+® on mineral metabolism, health status and excreta quality of broilers. This study used a completely randomized design (CRD) with 6 treatments and 6 replications (40 birds of each). The treatments were high nutrient diet (T1), T1 + silica+® 200 ppm (T2), low nutrient diet (T3), T3 + silica+® 200 ppm (T4), feed contain local feedstuff (rice bran) (T5), T5 + silica+® 200 ppm (T6). Parameters measured were minerals consumption, minerals retention, mineral content of the tibia, blood profile (erythrocytes, hemoglobin, hematocrit, leukocytes, differentiation of leukocytes and ratio H/L) and excreta quality (pH, water content and ammonia). The results showed that using silika+® 200 ppm increased (P <0.05) mineral consumption and excretion in low nutrient diet (T4), lowered (P <0.05) retention of Ca and Zn in high nutrient diet (T2), lowered (P<0.05) retention of Zn in low nutrient diet (T2), increased (P<0.05) Ca content in tibia bone in high nutrient diet (T2), increased Ca and Zn content in the tibia (P <0.05) in feed contain ricebran (T6), decreased the amount of fecal NH3 (P <0.05) in feed contain ricebran (T6), lowered E. coli in high nutriet diet (T2) and feed contain ricebran (T6). The conclusion of this study that silica+® could be used as feed additive to increase Ca and Zn deposition in tibia bone, lowering fecal NH3, lowering E. coli in ileum withouth any effect to the health status of broilers.